Three hearts and three lions - Anderson, Poul, 1926-2001 (Open Road Integrated Media, 2018)
Holger Carlsen is an American trained engineer in Denmark's anti-Nazi underground--until an explosion throws him into the past, a world of knights and Faerie, and into a great battle against the forces of chaos.